Pemenuhan Hak Konstitusional Warga Negara Indonesia: Studi Kasus Jaminan Kesehatan Nasional - Ulul Adzemi Romansyah, Ahmad Labib, Muridah Isnawati (Justitia Jurnal Hukum, 2017)
Health is an important factor for every citizen and thus require collateral for its survival. The objective is to determine the normative regulation and its efforts to investigate the implementation and proper normative adjustment pattern to give recognition, security, and protection of the constitutional rights of Indonesian citizens accordance with the mandate of Article 28 H paragraph (1), paragraph (2), paragraph ( 3) and Article 34 paragraph (1) and (2) 1945. The method used is normative juridical statute approach. The results obtained are finding normative regulations governing the national health insurance in the national social security system implemented social security administering bodies associated with membership and health services that are not appropriate if adjusted against the constitutional rights of Indonesian citizens. The remedies that can be taken in the event of problems regarding the implementation of the program is not health insurance through the judicial institution namely the National Human Rights Commission and the Ombudsman as well as through the courts at the district court level to the Supreme Court and the Constitutional Court.